The Art of Re-thinking : New Era for Arts Management - (:unkn) unknown (Taideyliopiston Sibelius-Akatemia, 2022)
The Art of Re-Thinking: New Era for Arts Management is a publication celebrating the 25th anniversary of the Arts Management department at the Sibelius Academy, Uniarts Helsinki. It offers 14 professional articles discussing the transformation of the Arts Management field, its relations to society, diversity and sustainability and topics related to creative work, entrepreneurship, marketing and cultural management. The writers represent the alumni, current staff and other professionals related to the Arts Management department at the Sibelius Academy, Uniarts Helsinki. The publication is one of the tangible outcomes of the Arts Management department’s re-thinking processes in the new era of Arts Management. The objective was to celebrate the versatility of Arts Management and people working in it. The publication is edited by Violeta Simjanovska, Head of the Arts Management Department and Toni-Matti Karjalainen, professor. The book shows how versatile and impactful the field of Arts Management is on the practices as well as on research and educational views in arts and culture. TABLE OF CONTENTS FOREWORD Emilie Gardberg INTRODUCTIONS 25 YEARS OF ARTS MANAGEMENT Violeta Simjanovska ABOUT OUR RESEARCH AND THIS BOOK Toni-Matti Karjalainen PART I: TRANSFORMATION OF ARTS MANAGEMENT 1. RE-THINKING ARTS MANAGEMENT RESEARCH AND EDUCATION – REFLECTIONS FROM A CONFERENCE TABLE Toni-Matti Karjalainen 2. PROFESSIONALISATION OF THE CULTURAL SECTOR THROUGH THE DEVELOPMENT OF ART/CULTURAL MANAGEMENT AND CULTURAL POLICY AS ACADEMIC, RESEARCH-BASED DISCIPLINES Milena Dragićević Šešić 3. MANAGING THE ARTS – MANAGING THE UNRESOLVED CONFLICT Tanja Johansson 4. ARTS AND ARTS MANAGEMENT STUDENTS IN ACADEMIA – CRITICAL THOUGHTS ON ENTREPRENEURIAL EDUCATION, KNOWLEDGE MANAGEMENT AND IDENTITY Kristina Kuznetsova-Bogdanovitsh 5. WE’RE BREAKING ALL THE RULES. EVEN OUR OWN RULES. Anna-Kaisa Rastenberger PART II: SOCIETY, DIVERSITY, AND SUSTAINABILITY 6. IN SEARCH OF AN ENHANCED SOCIETAL ROLE FOR THE ARTS – A CULTURAL SUSTAINABILITY POINT OF VIEW TO ARTS SECTOR RECONSTRUCTION Jenni Pekkarinen 7. REPOSITIONING POWER AND PRIVILEGE – IMPLEMENTING INTERSECTIONALITY AND ADAPTING ACTIVIST APPROACHES IN A MUSEUM Lilja Lehmuskallio 8. RE-THINKING OF CULTURAL POLICES ON DIVERSITY AND PARTICIPATION – A CASE STUDY ON THE PUBLIC ART ORGANIZATIONS IN THE HELSINKI CENTRAL AREA Violeta Simjanovska 9. CULTIVATING CULTURAL CHANGE – NOTES ON ART, ECOLOGY AND SOCIAL JUSTICE Taru Elfving PART III: CREATIVE WORK, ENTREPRENEURSHIP, MARKETING, AND CULTURAL MANAGEMENT 10. CREATIVE CLUSTERS AS CATALYSTS FOR LOCAL CULTURAL DEVELOPMENT Lidia Varbanova 11. CO-CREATION AND SUSTAINABILITY – THE NEW TRENDS IN ARTS MARKETING Annukka Jyrämä, Mervi Lounila & Kaari Kiitsak-Prikk 12. ART(IST) MANAGERS: CREATIVE PRACTITIONERS WORKING IN ARTS MANAGEMENT Sheila Murray 13. CREATIVE ECONOMY SUSTAINABILITY FRAMEWORK AND CONCENTRIC CIRCLES MODEL – NEW CONCEPTUAL TOOLS FOR ARTS AND CULTURAL MANAGEMENT
Keywords: taidehallinto